Suomi globaaleissa arvoketjuissa; Finland in Global Value Chains - Jyrki Ali-Yrkkö; Petri Rouvinen; Pekka Sinko; Joonas Tuhkuri (The Research Institute of the Finnish Economy (ETLA), 2016)
– This report uses an international input-output dataset to present an analysis of Finland's position in global value chains. The results show that intermediate products account for a larger share – some three-quarters – of Finnish exports than they do in most other countries. The share of foreign value added in Finnish export production is around the international average, but it has grown more rapidly than average. A higher share of foreign value added means that exports, on average, have less capacity to generate economic growth. The share of domestic value added has fallen particularly sharply in the fuel refining industry as well as in metal processing and the manufacture of metal products. The share of domestic value added has decreased more in Finnish than in Swedish industry. A value added based analysis changes the picture of Finland's most important trade partners and our international economic dependencies. Based on the analysis Finnish economic growth is heavily dependent on Chinese and US final demand. Over 10% of Finland's value added exports are ultimately destined for China, and almost the same proportion goes to the United States. However, the combined final demand from EU-28 countries still outweighs the demand from these two countries.
Keywords: F14; F6; F62; F68; 330; Globalisation; Value chain; Value network; Global; Value added; Intermediate; Input-output; Internationale Wirtschaft; Wertschöpfung; Internationale Produktion; Internationale Arbeitsteilung; Vorleistungen; Input-Output-Analyse; Finnland